Societies' psychological preparedness in the area of flood disaster at the Desa Sitiarjo Sumbermanjing Wetan - Faizatur Rahmi (Universitas Muhammadiyah Malang, 2016)
Natural disaster is an incident which is affecting to physical live and human psychology. Some of psychological effects are anxiety, depression, and Post Traumatic Stress Disorder. However, in fact, most of the government and private programs do not develop and give intervention toward psychological effects that might happen. This research aims to identify people's psychological preparedness in flood prone area at Sitiarjo Village, Sumbermanjing Wetan. This research is descriptive explorative. The population of this research is 110 people. This research uses accidental sampling to decide the sampling which is 80 people. This research uses an instrument in Psychological Preparedness for Disaster Threat Scale (PPDTS) that consists of 18 items. As a result, most of the respondents still have low psychological preparedness. So that, follow up is needed to be done by health worker to educate or train the psychological preparedness of people when the floods is coming.